Assessment of availability and pattern of utilization of institutional obstetric care by Venn exercises in rural Mysore, India - Siddalingappa, Hugara; R., Narayana Murthy M.; Mascarenhas, Maya; Hoogar, Varsha; T, Sulekha; Mony, Prem K (International Journal Of Community Medicine And Public Health, 2017)
Background: With improving indicators of maternal and child health (MCH) the increasing expenditure of the Government on health can be substantiated. But considering the growing number of hospitals in private sector, it is desirable to understand the preference of the rural population. Methodology: Four primary health centres (PHCs) were selected from the district by stratified random sampling based on their performance in MCH. Accredited social health activist (ASHA), female and male health workers of selected PHC were involved in Venn exercise to explore the availability and utilization pattern. Results: Villages nearer to district headquarter had plenty of options (hospitals) and institutions were fewer as they went away from headquarter. Maximum mothers used PHC for registration of pregnancy and basic antenatal care. Nearby community health centres (CHC), talluka and district hospitals were utilized by more than 90% mothers for intranatal care. Very few mothers preferred private hospitals for intranatal care because of high cost and unavailability of maternity benefits. In tribal PHC area, NGO hospital was preferred more than public sector due to preference of lady doctor. Cost of care was minimum with decreasing distance from district/talluka hospital. Private hospitals were charging two to three times the expenditure in public sector for the same service. Conclusion: Delivery facility was available within 10 to 15 Km distance of each village and government sector was the leading obstetric care provider in the study area.